Financial Literacy Initiatives entails Behavioral Insight Approach: Ideas - Dr. Rajni Rajan Chauhan (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
Behavioral researches evident that retail investors possess irrational decisions behavior and suffering from psychological, cognitive and social biases that influence decision. Individual tends to employ heuristics and practice personal biases to simplify decision situation instead of accessing to comprehensive information.Though various financial literacy programmes has been initiated in different countries, yet the studies evident failure to assure desired outcomes of such initiatives in consumers. The consistent financial interventions are need of an hour to achieve desired results. Regulatory bodies are facing challenge of developing simple and cost effective financial educational programme in the light of Behavioral Insights(BI). The present study aims at suggesting usage of behavioral insights in financial literacy initiatives for efficacy in consumer behavior based on literature review and OECD recommendations.